(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Respiratory diseases constitute a significant part of global health challenges, affecting millions of people across all age groups and leading to substantial morbidity and mortality. Improved understanding and awareness of the importance of early diagnosis have been at the forefront of respiratory medicine, as timely detection of diseases such as asthma, chronic obstructive pulmonary disease, tuberculosis, pneumonia, interstitial lung disease, and lung cancer is directly associated with better treatment outcomes and reduced disease burden. The nature of respiratory diseases often involves progressive decline in lung function and general health if left undetected or untreated; hence, the early recognition of symptoms and immediate medical evaluation forms the basis of effective management and prevention of complications.